Occupational skin and respiratory diseases among hairdressers - Leino, Timo; Tammilehto, L; Hytönen, M; Sala, E; Paakkulainen, H; Kanerva, L (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVES ': 'The occurrence and causes of hairdressers' occupational skin and respiratory diseases were studied.' ' METHODS ': 'Of a random sample of 500 female hairdressers aged 15-54 years, 355 were available for study. Of the 189 reporting work-related skin and respiratory symptoms in a computer-aided telephone interview on exposure and health, 130 underwent a physical examination, lung function tests, prick and patch testing, and nasal and lung provocation tests. An occupational disease was diagnosed when the causality between exposure and disease was probable and the clinical tests supported the diagnosis.' ' RESULTS ': 'The telephone interview revealed a life-time prevalence of 16.9% for hand dermatoses, 16.9% for allergic rhinitis, and 4.5% for asthma among the hairdressers. In the clinical investigations, the prevalence was 2.8% for occupational dermatoses, 1.7% for occupational rhinitis, and 0.8% for occupational asthma. Ammonium persulfate caused 90% of the respiratory diseases and 27% of the hand dermatoses. Paraphenylenediamine, natural rubber latex, and skin irritation were also causes of hand dermatitis. Allergy to human dandruff (8.6%) and Pityrosporum ovale (12.1%) was common. Previously diagnosed atopic diseases increased the risk for occupational skin or respiratory disease 3-fold (odds ratio 2.9, 95% confidence interval 1.1-7.9). Of the cases, 37.5% (6 of 16 persons) had to change occupations during a 3-year follow-up.' ' CONCLUSION ': 'Work-related skin and respiratory symptoms are common among hairdressers. Often a specific cause (eg, ammonium persulfate) can be found if occupational diseases are suspected and diagnosed. Hairdressers with atopic diseases are at risk of developing occupational skin and respiratory diseases.
Keywords: allergy; asthma; atopy; dermatitis; koilonychia; laryngitis; prevalence; rhinitis